Comparison of Echocardiographic Changes Between Surgery and Medication Treatment in Patients With Primary Aldosteronism - Tomomi Ueda; Yuya Tsurutani; Jun Osada; Kosuke Inoue; Yoshitomo Hoshino; Masato Ono; Kazuki Nakai; Jun Saito; Kazuhiko Yumoto; Tetsuo Nishikawa (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Primary aldosteronism can cause cardiac dysfunction, including left ventricular hypertrophy, left ventricular diastolic dysfunction, and left atrial enlargement. A few studies have compared the cardioprotective effects between surgery and medication for primary aldosteronism, although most have not adjusted for baseline disease status. In this study, we investigated the difference in cardiovascular outcomes between surgery and medication treatment for primary aldosteronism after adjusting for baseline clinical characteristics, including aldosterone level and pretreatment echocardiographic information. Methods and Results We retrospectively analyzed 220 patients diagnosed with primary aldosteronism who underwent adrenalectomy (n=144) or medication treatment (n=76) between 2009 and 2019. Echocardiographic changes were evaluated pretreatment and 1 year posttreatment. The surgery group had lower potassium, lower plasma renin activity, and higher plasma aldosterone concentration than the medication group, indicating a severe primary aldosteronism phenotype in the former. The decrease in left ventricular mass index after treatment was significantly greater in the surgery group than in the medication group (P=0.047). However, this relationship was not noted after multivariable regression analysis (standard β=−0.08, P=0.17). Additionally, decreased parameter values related to left ventricular diastolic dysfunction and left atrial enlargement were not different between the groups. Pretreatment echocardiographic values were most associated with changes in all echocardiographic parameters. The findings were consistent in the propensity score‐matched analysis. Conclusions This study's findings suggest that there is no difference in cardioprotective efficacy between surgical and medication treatment under similar disease severity; however, it should be considered that several study participants with severe hyperaldosteronism were managed surgically.